Changes in the neuromuscular and cardiorespiratory performance during the competitive season in early and late matured 14-15- year old male ice hockey players - Laaksonen, Antti (2012)
Ice hockey as a game is metabolically very demanding, and well trained aerobic and anaerobic metabolism is needed. Adolescent players have their own schedule according to growth and maturation. There might be huge differences at growth and maturity during pubertal and adolescent years. The aim of this study was to examine changes in the performance profile during the competitive season and compare changes in performance profile between early and late matured subjects. The measurements were done during the competitive season (Spring 2011 – Spring 2012). Subjects of this study were 14-15-year old male ice hockey players, who were competing at the highest national level. The measurements were done four times during the competitive season: PRE before preparatory period, MID1 between preparatory and competitive period, MID2 on Christmas break and POST after the competitive season. Neuromuscular (maximal and explosive strength of lower- and maximal strength and muscle endurance of upperbody and trunk), cardiorespiratory (maximal graded bicycle ergometer test) and on ice skills (skating- and stickhandling track) were tested. The neuromuscular performance improved significantly (p<0.05) between PRE to POST in maximal bilateral isometric leg extension (from 3425±578N to 3847±696N) and maximal trunk extension and flexion (trunk extension from 85.8 ±12 kg to 98.7±14 kg and trunk flexion from 68.4±13 to 74.9 ± 15 kg). Between the group comparison the early matured group were stronger in all measurements. No differences were found in the speed and explosive strength tests. The cardiorespiratory performance measured by peak power (W) in the maximal graded bicycle ergometer changed significantly (p<0.05) between PRE to POST (from 282,9±26 W to 298±26 W). The early matured group had significantly (p<0.05) higher peak power compared to late matured group in all measurements. In relative change during competitive season, the late matured subjects improved performance more compared to the early matured group in strength, speed strength, speed and on ice skills. The physical performance tests showed that subjects were able to improve and maintain their physical performance level over the competitive season. According to the present results, the early matured subjects were bigger and stronger compared to the late matured group. In speed, on ice skill and explosive strength tests, no differences were found. This information suggests that early matured players have an advantage at the game, because they are bigger and stronger, and are as fast and skilled as late matured players. Late matured players improved physical performance level and on ice performance more compared to early matured subjects. According to this information, it may be too early to jugde players at this age, because growth is still going on.